Pengaruh Sistem Sirkulasi terhadap Produksi Biogas dari Kotoran Sapi dan Limbah Cair Tahu - M. Zhafran Zharif Amrin; Rosalina Rosalina; Eko Supriadi (Student Research Journal, 2025)
To improve the performance of a biogas Digester, several methods can be employed, one of which is by adding a circulation system [1]. Circulation in the Digester helps distribute the substrate and microorganisms evenly [2], thereby accelerating biological reactions and releasing gas, thus enhancing biogas productivity [3]. The objective of this study is to design and analyze the impact of a circulation system on a biogas Digester during the fermentation of liquid tofu waste and cow manure. The research was conducted in two stages: first, designing the Digester, and second, operating the Digester in two steps. The first step involved batch fermentation for 14 days to condition the degrading microorganisms. The second step involved continuous fermentation for 16 days, operated with a circulation system at varying rates of 0, 30, 60, and 90. The variables studied included digester pressure, CH4 concentration, and COD reduction. The results showed that circulation increased biogas productivity, with the best variation achieved using 90 circulation, resulting in a pressure of 0.19 kg/cm², 58% CH4, and 33.33% COD reduction.